Transformations in east-central Europe from 6000 to 3000 BC - Nowak, Marek (Documenta Praehistorica, 2006)
In the sixth, fifth and fourth millennium BC, in the basins of the Vistula andthe Oder, extremely complex economic, social and ideological transformations took place. They consisted in the emergence and expansion of new systems of circulating information ('communicative communities'). The majority of these were connected with the Neolithic. The process involved a constant clash between foreign and local patterns. The latter, over time, prevailed. Hence the ultimate dominance of Neolithic communicative communities in the eastern part of Central Europe around the middle of the fourth millennium was essentially a local development. Nonetheless, a considerable portion of the territory continued to remain outside their influence. Therefore, throughout the three millennia, Mesolithic communicative communities not only gradually merged with or evolved into Neolithic ones. They also embraced such transformations, mainly concerning thematerial culture and ideology, which were completely independent from the advances of the Neolithic, or could have been competitive in relation to them.
Keywords: Poland; Poljska; archaeology; arheologija; mezolitik; neolitik; družbeni razvoj; demografski razvoj; družbene spremembe